A Fast Intra Prediction for H.264/AVC Based on SATD and Prediction Direction. (2016) - Mathew, Deepa; Binish, M.C.
Abstract: To improve the coding efficiency of H.264/AVC, the encoder computes Rate Distortion (RD) costs of all possible intra coding modes to decide the optimum mode, this leads to high computational complexity. A fast intra prediction mode decision method to reduce the computational complexity is presented in this paper. The method employs the prediction directions and the Sum of Absolute Transformed Difference (SATD) of the reconstructed surrounding pixels and the block content to remove the less likely prediction modes from the Rate Distortion Optimization (RDO) computation. A block type skip method is also presented to further improve the performance. The experimental results show that the proposed method can reduce the coding time effectively with slight video quality degradation and bit rate increment.